Robust and Broadband Optical Coupling by Topological Waveguide Arrays. Issue 2 (13th January 2020) - Song, Wange; Sun, Wenzhao; Chen, Chen; Song, Qinghai; Xiao, Shumin; Zhu, Shining; Li, Tao
Abstract: Photonic topological states have been exploited to give rise to robust optical behaviors that are quite insensitive to local defects or perturbations, which provide a promising solution for robust photonic integrations. Specifically, for example, optical coupling between waveguides is a universal function in integrated photonics. However, the coupling performance usually suffers from high structure‐sensitivity and challenges current manufacturing for massive production. Here, the topological edge state in a finite Su–Schriffer–Heeger modeled optical waveguide array is explored and robust optical coupling (e.g., directional coupling and beam splitting) is demonstrated, which is quite insensitive to structural variations. It is experimentally proved that even a large discrepancy (21–26% structural deviation) in silicon waveguides gaps has little influence on optical coupling (>90% performance), while conventional counterparts totally break down. Moreover, thanks to such a topological design, the devices show much broader working bandwidth (≈10 times performance improvement) than the conventional ones, greatly favoring the photonic integrations. This work would inspire new families of optical devices with robust and broadband properties that can excite more interesting and useful exploration in both fields, and possibly open a new avenue toward topological devices with unique properties and functionalities. Abstract : A robust design of optical directional coupler and beam splitter is proposed using the coupling of edge states in a topological waveguide array. The devices are implemented in silicon waveguide platform with robust and broadband performances well confirmed by comparing with conventional devices. This topological design would pave the way for massive photonic integrations with loose fabrication requirement.